Analisis Frasa dalam Kisah Sejarah pada Buku Ilmu Pengetahuan Sosial Kelas X Kurikulum Merdeka - Naazil Maharani An Nuur; Arfiatun Astia Ningrum; Darojatin Mansuriniati; Benedikta Agusta Kandam; Asep Purwo Yudi Utomo; Ristiyani Ristiyani (Pusat riset dan Inovasi Nasional, 2023)
This study focuses on the analysis of phrases contained in the text of historical stories in class X textbooks of Social Sciences in the independence curriculum. This study uses a qualitative descriptive method and data collection techniques used are listening techniques, observation techniques, and note taking techniques. In this analysis, the author analyzes the phrases in four historical narrative texts entitled Mohammad Hatta: